‘Green’ silver nanoparticles combined with tyrosol as potential oral antimicrobial therapy - Souza, José Antonio Santos [UNESP]; do Amaral, Jackeline Gallo [UNESP]; Monteiro, Douglas Roberto [UNESP]; Fernandes, Renan Aparecido [UNESP]; Fernandes, Gabriela Lopes [UNESP]; Gorup, Luiz Fernando; de Souza Neto, Francisco Nunes; de Camargo, Emerson Rodrigues; Agostinho, Alessandra Marçal; Barbosa, Debora Barros [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Elsevier, 2024)
Objectives: This study aimed to evaluate silver nanoparticles (AgNPs) obtained by a ‘green’ route associated or not to tyrosol (TYR) against Streptococcus mutans and Candida albicans in planktonic and biofilms states. Methods: AgNPs were obtained by a ‘green’ route using pomegranate extract. The minimum inhibitory concentration (MIC) against S. mutans and C. albicans was determined for AgNPs and TYR combined and alone, and fractional inhibitory concentration index (FICI) was calculated. Single biofilms of C. albicans and S. mutans were cultivated for 24 h and then treated with drugs alone or in combination for 24 h. Results: AgNPs and TYR were effective against C. albicans and S. mutans considering planktonic cells alone and combined. The MIC values obtained for C. albicans was 312.5 µg/mL (AgNPs) and 50 mM (TYR) and for S. mutans was 78.1 µg/mL (AgNPs) and 90 mM (TYR). The combination of these antimicrobial agents was also effective against both microorganisms: 2.44 µg/mL/0.08 mM (AgNPs/TYR) for C. albicans and 39.05 µg/mL /1.25 mM (AgNPs/TYR) for S. mutans. However, synergism was observed only for C. albicans (FICI 0.008). When biofilm was evaluated, a reduction of 4.62 log10 was observed for S. mutans biofilm cells treated with AgNPs (p < 0.05, Tukey test). However, the addition of TYR to AgNPs did not improve their action against biofilm cells (p > 0.05). AgNPs combined with TYR demonstrated a synergistic effect against C. albicans biofilms. Conclusions: These findings suggest the potential use of AgNPs with or without TYR against C. albicans and S. mutans, important oral pathogens. Clinical significance: AgNPs obtained by a ‘green’ route combined or not with TYR can be an alternative to develop several types of oral antimicrobial therapies and biomaterials.
Keywords: Biosynthesis; Candida albicans; Silver nanoparticles; Streptococcus mutans; Tyrosol